Job satisfaction, structure of working environment and firm size - Aysit Tansel; Saziye Gazioglu (Koç University-TÜSIAD Economic Research Forum (ERF), 2022)
Employees' wellbeing is important to the firms. Analysis of job satisfaction may give insight into various aspect of labor market behavior, such as worker productivity, absenteeism and job turn over. Little empirical work has been done on the relationship between structure of working environment and job satisfaction. This paper investigates the relationship between working environment, firm size and worker job satisfaction. We use a unique data of 28,240 British employees, Workplace Employee Relations Survey. In this data set the employee questionnaire is matched with the employer questionnaire. Four measures of job satisfaction considered are satisfaction with influence over job, satisfaction with amount of pay, satisfaction with sense of achievement and satisfaction with respect from supervisors. They are all negatively related to the firm size implying lower levels of job satisfaction in larger firms. The firm size in return is negatively related to the degree of flexibility in the working environment. The small firms have more flexible work environments. We further find that, contrary to the previous results lower levels of job satisfaction in larger firms can not necessarily be attributed to the inflexibility in their structure of working environment.
Keywords: J21; J28; J29; J81; 330; Job Satisfactions; Firm Size; Working Environment; Linked Employer-Employee data; Britain